Nurse educators' use and experiences with high-fidelity simulation in nursing programmes at a South African private higher education institution - Me Elize Powell; Belinda Scrooby; Anneke van Graan (Elsevier, 2020)
Background: Student nurses' clinical exposure is insufficient for clinical skills development due to limited available clinical placements and learning opportunities, and reduced time spent with patients because of hospitalisation time, restrictions from medical aid schemes and less invasive procedures being performed on patients. Simulation training, as an alternative teaching-learning method, creates an environment where collaboration and interactive participation take place, clinical skills are developed and students are prepared for the nursing profession. Objective: The objective of the study was to describe nurse educators' current use and experiences with high-fidelity simulation in nursing programmes at a South African private higher education institution. Methodology: A descriptive quantitative research design. The data were collected by means of an electronic teaching-learning feedback questionnaire developed by Jones (2005). Results: With an all-inclusive sampling method the respondents indicated that their experiences with high-fidelity simulation ranged between being a novice (n = 29, 42.03%), and an advanced beginner (n = 20, 28.99%). Only 23.19% of respondents indicated they were competent with using high-fidelity simulation and three (4.35%) indicated they were proficient in using high-fidelity simulation. Respondents indicated they had more experience using low-fidelity simulation due to not having high-fidelity simulation equipment or because they did not feel competent and confident using the equipment. Conclusion: It became evident that nurse educators' experience (more than 15 years) played an important role in their comfort level in integrating technology into the classroom and the comfort level towards utilising high-fidelity simulation as d-values ranged between 0.44 and 0.58.